2017
DOI: 10.5897/ajmr2016.8407
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of an enzyme-linked immunosorbent assay (ELISA) using a soluble recombinant nucleoprotein for the detection of antibodies to avian influenza virus

Abstract: Avian influenza (AI) causes significant impact on industrial poultry farming, besides infecting a variety of vertebrates. The detection of antibodies against viral antigens by serological methods is important for the epidemiology, control and prevention of AI because their high simplicity and speed for assaying a large number of samples. Obtaining antigenic preparations used for detection of anti-avian influenza virus (AIV) antibodies usually requires complex and expensive procedures and Escherichia coli syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Avian influenza is a significant viral disease worldwide. H9N2 viruses have relatively fewer pathogenesis types, whereas over the past decade, there have been many reports of damage or loss in these strains (3,14,33). NP is the most important influenza virus internal protein, which can help detect influenza viruses A, B, and C. Previously research have shown that NP can be a proper target for the antiviral drugs development against influenza virus different types by stimulating immune responses (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Avian influenza is a significant viral disease worldwide. H9N2 viruses have relatively fewer pathogenesis types, whereas over the past decade, there have been many reports of damage or loss in these strains (3,14,33). NP is the most important influenza virus internal protein, which can help detect influenza viruses A, B, and C. Previously research have shown that NP can be a proper target for the antiviral drugs development against influenza virus different types by stimulating immune responses (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that patients benefit from antiviral treatment, especially in the first 48 hours of illness (16). Currently, serological diagnostic techniques such as agar gel propagation (AGP), hemagglutination inhibition, and enzyme-linked immunosorbent assay (ELISA) are considered as important tools for the antibodies detection against viral antigens (17). These techniques are common and relatively inexpensive, and generate results more rapidly (18,19).…”
Section: Introductionmentioning
confidence: 99%